1997
DOI: 10.1017/s0266467400010609
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of bulk precipitation in southwestern Viti Levu, Fiji

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Cambridge University Press is collaborating with JSTOR to digitize, preserve and extend access to Journal of Tropical Ecology.http://www.jstor.org ABSTRACT. The amounts and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…If [Cl À ] tot,i < 200 lM, all Cl À is assumed to come from atmospheric deposition. The value of [Cl À ] rain = 200 lM derives from the assumption that rainfall in the region has an average chloride concentration of 100 lM (Eklund et al, 1997;Waterloo et al, 1997;Fujita et al, 2000;Kyoung Lee et al, 2000) and the evapotranspiration factor is around 2. Inputs from Cl À bearing minerals such as amphiboles are believed to be minor and in any case are not well constrained by our data.…”
Section: Sources Of Solutesmentioning
confidence: 99%
“…If [Cl À ] tot,i < 200 lM, all Cl À is assumed to come from atmospheric deposition. The value of [Cl À ] rain = 200 lM derives from the assumption that rainfall in the region has an average chloride concentration of 100 lM (Eklund et al, 1997;Waterloo et al, 1997;Fujita et al, 2000;Kyoung Lee et al, 2000) and the evapotranspiration factor is around 2. Inputs from Cl À bearing minerals such as amphiboles are believed to be minor and in any case are not well constrained by our data.…”
Section: Sources Of Solutesmentioning
confidence: 99%
“…The reason for the high value of stemflow at our site could be related to the crown morphology of the dominant species, C. sieboldii, which has inclined branches and concave shaped leaves. In addition, wind speed [23] and very high rainfall [43] can also affect the stemflow rate. On Okinawa, windstorms, particularly typhoon events, are very frequent and this may be an important cause of the high fraction of stemflow.…”
Section: Precipitation Partitioningmentioning
confidence: 99%
“…In addition, typhoons are frequent. Typhoon events can bring a large amount of rainfall with high concentrations of Na and Cl to the island [13,22,43]. Comparing the chemistry of precipitation and runoff at 47 forested sites in the whole of Japan, Iwatsubo et al [20] found that concentrations of Cl and Na in rainfall and runoff were significantly and negatively correlated to distance from the sea.…”
Section: Nutrient Concentration and Fluxes In Precipitation Componentsmentioning
confidence: 99%
“…Although the work in 1990-1991 was conducted during a period for which the rainfall distribution resembled the longterm average at Nabou [Waterloo, 1994], the simulations were carried out using climatic data collected at the more inland site of Tulasewa. Rainfall in southwestern Viti Levu shows a high interannual variation (864-2983 mm yr -• at Nadi) and increases with distance from the coast (from 1796 mm near the coast to 2113 mm at Tulasewa in 1990 [Waterloo et al, 1997]). The annual transpiration of the grass may vary considerably with rainfall and the length of the dry and wet seasons [Riou, 1984], as these particularly affect the magnitude of the LAI (Figure 8).…”
Section: Afforestationmentioning
confidence: 99%